Incentives that saved lives: Government regulation of accident insurance associations in Germany, 1884 - 1914 - Timothy W. Guinnane; Jochen Streb (Yale University, Economic Growth Center, 2012)
The German government introduced compulsory accident insurance for industrial firms in 1884. This insurance scheme was one of the main pillars of Bismarck's famous social insurance system. The accident-insurance system achieved only one of its intended goals: it successfully compensated workers and their survivors for losses due to accidents. The accident-insurance system was less successful in limiting the growth of work-related accidents, although that goal had been a reason for the system's creation. We trace the failure to stem the growth of accidents to faulty incentives built into the 1884 legislation. The law created mutual insurance groups that used an experience-rating system that stressed group rather than firm experience, leaving firms with little hope of saving on insurance contributions by improving the safety of their own plants. The government regulator increasingly stressed the imposition of safety rules that would force all firms to adopt certain safety practices. Econometric analysis shows that even the flawed tools available to the insurance groups were powerful, and that more consistent use would have reduced industrial accidents earlier and more extensively.
Keywords: N33; G22; H55; 330; Social insurance; accident insurance; workman's compensation; regulation; Unfallversicherung; Ökonomischer Anreiz; Arbeitsschutz; Geschichte; Deutschland (bis 1945)